Metabolic profiling of silymarin constituents in urine and feces of healthy volunteers: A 90-day study. (January 2023) - Lněničková, Kateřina; Vrba, Jiří; Kosina, Pavel; Papoušková, Barbora; Mekadim, Chahrazed; Mrázek, Jakub; Sova, Milan; Sovová, Eliška; Valentová, Kateřina; Křen, Vladimír; Kouřilová, Pavla; Vrbková, Jana; et al.
Graphical abstract: Highlights: Silymarin metabolism was studied in 33 volunteers taking 2 × 200 mg/day for 90 days. Metabolic profiles of flavonolignans and taxifolin were analyzed using UHPLC-MS. Inter-individual differences in metabolite levels in urine and feces were noted. Relation between metabolism, age, BMI, smoking, or gut microbiota was evaluated. Abstract: This study examined the metabolism of flavonolignans and taxifolin in 33 healthy adult male volunteers, who received 200 mg of silymarin orally twice daily for three months. First-morning urine and feces collected on days 10 and 90 were analyzed by UHPLC-MS and bacterial composition of feces was investigated by Next Generation Sequencing. The analyses revealed 5/4 types of flavonolignan/taxifolin metabolites in urine and 13/10 types of metabolites in feces, with large differences in total metabolite levels in both urine and feces observed among individual participants. In urine, 21 and 23 participants showed some increase in the total amount of flavonolignan and taxifolin metabolites, respectively, on day 90 compared with day 10. In feces, some correlation was found between the amount of metabolites and the composition of the intestinal microbiota. In conclusion, silymarin flavonolignans and taxifolin undergo multiple biotransformation reactions, and the metabolic profiles of the constituents considerably vary among individuals.